2010
DOI: 10.1186/1476-072x-9-61
|View full text |Cite
|
Sign up to set email alerts
|

Gumbel based p-value approximations for spatial scan statistics

Abstract: BackgroundThe spatial and space-time scan statistics are commonly applied for the detection of geographical disease clusters. Monte Carlo hypothesis testing is typically used to test whether the geographical clusters are statistically significant as there is no known way to calculate the null distribution analytically. In Monte Carlo hypothesis testing, simulated random data are generated multiple times under the null hypothesis, and the p-value is r/(R + 1), where R is the number of simulated random replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 34 publications
2
57
0
Order By: Relevance
“…The maximum likelihood ratio window is the most likely spatial cluster of gastric cancer morbidity and Monte Carlo simulation was used to calculate the p value. The null hypothesis is that the gastric cancer morbidity is the same in all the sub-districts, compared with alternative hypothesis that the gastric cancer morbidity within the window is significantly higher than that outside (Kulldorff 1997;Abrams et al 2010). Sometimes it is interesting to see whether a significant cluster can decompose to several non-overlapping subclusters.…”
Section: Spatial Scan Statisticmentioning
confidence: 99%
“…The maximum likelihood ratio window is the most likely spatial cluster of gastric cancer morbidity and Monte Carlo simulation was used to calculate the p value. The null hypothesis is that the gastric cancer morbidity is the same in all the sub-districts, compared with alternative hypothesis that the gastric cancer morbidity within the window is significantly higher than that outside (Kulldorff 1997;Abrams et al 2010). Sometimes it is interesting to see whether a significant cluster can decompose to several non-overlapping subclusters.…”
Section: Spatial Scan Statisticmentioning
confidence: 99%
“…The Gumbel‐based p ‐value is calculated as the probability that the test statistic is larger than the observed value, assuming the distribution of the test statistic under the null is Gumbel with the location and scale parameters estimated from MC replications. Abrams et al also showed that 99 replications for Gumbel approximation have about the same power with 999 replications for MC hypothesis testing. For comparison, we also list likelihood ratio test statistics calculated using the LRO‐based method for the clusters detected using the STO‐based method in Table .…”
Section: Applicationmentioning
confidence: 89%
“…The reason for this is a theorem of Piterbarg (1996). The Gumbel distribution has also been used previously by Abrams et al (2010) to obtain an approximation to the spatial scan statistic. In the second approach, the threshold h emp is obtained as the percentile of the empirical distribution function of the maxima.…”
Section: Determining the Thresholdmentioning
confidence: 99%